Traduction anthroponymique et préservation de la symbolique des noms propres dans les œuvres littéraires. Etude de cas : l’école de la médisance - Meriam Benlakdar (Multilinguales)
The present study aims to analyse the symbolic representations and characteristics associated with proper names used in literary works, particularly in Sheridan’s « The School for Scandal » (1777) and to identify the techniques adopted to translate these proper names while preserving their symbolic and satirical dimensions. Through a comparative methodology, we will examine the challenges posed by the cultural, linguistic, and phonetic differences that exist between the source language and the target language. The results of this study offer a perspective on the possibilities linked to anthroponymic translation and the choices of translators in the context of intercultural translation, while contributing to the understanding of the role of literary proper names in the identification, characterization, and representation of characters in literary works.